PENGARUH KEPUASAN KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOMINFO KOTA MEDAN - Yudhistira, Prima; Daryana, Aditiya Pratama; Girsang, Deddy Ray; Damanik, M.A. Jaya (Jurnal Manajemen dan Bisnis, 2025)
This study discusses issues related to low levels of job satisfaction, work discipline, and the quality of the work environment, which impact suboptimal work results and frequent delays in task completion. The purpose of this research is to analyze the effects of job satisfaction, work discipline, and work environment on employee performance at the Communication and Information Office (KOMINFO) of Medan City. This study uses a quantitative approach with a Likert scale to measure the variables being examined. Data were collected through questionnaires distributed to all permanent employees of the Medan City KOMINFO Office, totaling 56 individuals. Validity and reliability tests were conducted to ensure the accuracy of the data. Data analysis was performed using multiple linear regression, hypothesis testing, and the coefficient of determination. The results show that: (1) job satisfaction partially affects employee performance at the Medan City KOMINFO Office; (2) work discipline partially affects employee performance; (3) the work environment partially influences employee performance; and (4) simultaneously, job satisfaction, work discipline, and work environment together have a positive and significant effect on employee performance at the Medan City KOMINFO Office.